Tourist Attraction and Tourist Motivation in The Patuha Mountain Area, West Java - Dema Amalia Putri; Maria Hedwig Dewi Susilowati; Jarot Mulyo Semedi (Faculty of Geography, Universitas Gadjah Mada, 2021)
The Bandung Regency Spatial Plan for 2007-2027 regulates The Patuha Mountain Area as one of the regions that have a special role in the tourism sector. This research was conducted to find out the attractiveness value and motivation of tourists on tourist attractions as well as the relationship between them in The Patuha Mountain Area. Assessment of tourist attractiveness value was based on the completeness of attraction, tourist facilities, and accessibility. Meanwhile, tourist motivation was based on tourist preferences, tourist needs, and tourist travel status. The variables were analyzed using spatial analysis and chi-square test statistics. The results indicated that the high attractiveness value has a nodal destination system, while medium and low attractiveness value has a linear destination system. Tourist motivation was being dominated by flashpacker types. Tourists who visited The Patuha Mountain Area are not being influenced by the attractiveness value of tourist attractions. Although tourist attraction has complete tourist facilities, tourists only focus on the attraction compared to the tourist facilities and accessibility.